The Strategy of Tourism Development on Woven Craftsmen Group in Tasikmadu Thematic Tourism Village, Malang City - Arifin, Ahmad Zaenal; Purnomo, Agus (Jurnal Pendidikan Ilmu Sosial, 2022)
This research is located in the Tasikmadu thematic tourism village, aiming to formulate the right strategy for developing the weaving thematic tourism village in Tasikmadu, Malang City. This study uses quantitative methods with SWOT analysis. There are eight respondents and one key respondent. The results of this study indicate that the strategy used in the development of the thematic weaving village in Tasikmadu is located in the quadrant I position. The aggressive strategy used by Tasikmadu weaving artisans is to improve the skills and creativity of better weaving artisans so that they have the opportunity to increase sales of handicrafts, utilizing State University Malang as a partner for product marketing on an international scale, as well as weaving artisans in Malang City which are still minimal, affordable prices, and product designs that can adapt to consumers so that it becomes a promising business opportunity. This research helps provide the right strategy for developing thematic woven tourism villages in Tasikmadu.